Aperçu biologique du Platypus cylindrus (Fabricius, 1792) (Coleoptera, Curculionidae : Platypodinae) dans les galeries du bois de chêne-liège (Quercus suber L.) - Belhoucine, Latifa; Bouhraoua, Rachid Tarik; Dahane, Belkheir; PUJADE-VILLAR, JULI; Tarik Bouhraoua, Rachid (Orsis: organismes i sistemes, 2011)
The study of the biology of the insect Platypus cylindrus (Fabricius, 1792) in the galleries of the wood of cork oak was studied on the level of the national forest of M’Sila, littoral Oranian with semi arid climate. For that, 3 trees strongly infested by the pest were cut down between December 2007 and July 2008. The dissection of the 14 wood discs having a volume of 53 dm3 , enabled us to count 2920 individuals with an average density of 55 individuals/dm3 . At any time of the year, at least two stages of each population coexist together with fluctuating rates. The adult insects as well as the larvae are present throughout the period of experimentation. These last constitute the majority of the taken population (78%). The eggs and the nymphs, almost absent for wintry time appear in spring. Some morphological characteristics of larvae and eggs are set.
Keywords: Algeria.; biology; Cork oak; forest of M’Sila; Platypus cylindrus

Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber

Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber